The relationship between organisational stressors and mental wellbeing within police officers: a systematic review - Demou, Evangelia (2019)
Background: Occupational stressors in police work increase the risk for officer mental health morbidities. Officers’ poor mental wellbeing is harmful to the individual, can affect professionalism, organisational effectiveness, and public safety. While the impact of operational stressors on officers’ mental wellbeing is well documented, no review has systematically investigated organisational stressor impacts. This study aimed to conduct a systematic review to assess the relationship between organisational stressors and police officer mental wellbeing. Methods: Systematic review conducted following PRISMA and Cochrane Collaboration guidelines. Literature search was undertaken from 1990 to May 2017 on four databases (EBSCOHOST Medline/SocINDEX/PsycINFO/OVID Embase) and grey literature. Included articles were critically appraised and assessed for risk of bias. Narrative and evidence syntheses were performed by specific mental health outcomes. Results: In total, 3571 results were returned, and 15 studies met the inclusion criteria. All included studies were published in English between 1995 and 2016, had cross-sectional study designs, spanned across four continents and covered 15,150 officers. Strong evidence of significant associations was identified for organisational stressors and the outcomes of: occupational stress, psychiatric symptoms/psychological distress, emotional exhaustion and personal accomplishment. The organisational stressors most often demonstrating consistently significant associations with mental health outcomes included lack of support, demand, job pressure, administrative/organisational pressure and long working-hours. Conclusions: This review is the first to systematically examine organisational stressors and mental health in police officers. Organisational stressors that can be targeted by interventions and policy changes to secure officer wellbeing, a healthy work environment, and benefits to the organisation and the public are identified